How willing are parents to improve pedestrian safety in their community?. Issue 12 (2nd December 2003) - Bishai, D; Mahoney, P; DeFrancesco, S; Guyer, B; Carlson Gielen, A
Abstract : Study objective: To determine how likely parents would be to contribute to strategies to reduce pedestrian injury risks and how much they valued such interventions. Design: A single referendum willingness to pay survey. Each parent was randomised to respond to one of five requested contributions towards each of the following activities: constructing speed bumps, volunteering as a crossing guard, attending a neighbourhood meeting, or attending a safety workshop. Setting: Community survey. Participants: A sample of 723 Baltimore parents from four neighbourhoods stratified by income and child pedestrian injury risk. Eligible parents had a child enrolled in one of four elementary schools in Baltimore City in May 2001. Main results: The more parents were asked to contribute, the less likely they were to do so. Parents were more likely to contribute in neighbourhoods with higher ratings of solidarity. The median willingness to pay money for speed bumps was conservatively estimated at $6.43. The median willingness to contribute time was 2.5 hours for attending workshops, 2.8 hours in community discussion groups, and 30 hours as a volunteer crossing guard. Conclusions: Parents place a high value on physical and social interventions to improve child pedestrian safety.